2021
DOI: 10.1111/jsr.13400
|View full text |Cite
|
Sign up to set email alerts
|

Do sleep changes mediate the anti‐depressive and anti‐suicidal response of intravenous ketamine in treatment‐resistant depression?

Abstract: Summary Sleep disturbances are commonly reported in patients with treatment‐resistant depression (TRD). Available data have shown that intravenous (IV) ketamine is an effective treatment for patients with TRD and growing data suggest ketamine may improve overall sleep architecture. In the present study, we evaluated whether changes in sleep symptoms mediated the anti‐depressive and/or anti‐suicidal effects of IV ketamine and whether improvement in sleep correlated with a higher likelihood of achieving response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Sleep improvements also mediate the effects of ketamine on SI, owing to reductions in insomnia, sleep restlessness, early morning awakening, and nocturnal wakefulness ( Rodrigues et al, 2021 ; Vande Voort et al, 2016 ). Ketamine's sleep-improving effect is likely a multifactorial process involving the normalization of the circadian sleep/wake system.…”
Section: Remediating Stress-related Endophenotypes Of Suicide: a Pote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep improvements also mediate the effects of ketamine on SI, owing to reductions in insomnia, sleep restlessness, early morning awakening, and nocturnal wakefulness ( Rodrigues et al, 2021 ; Vande Voort et al, 2016 ). Ketamine's sleep-improving effect is likely a multifactorial process involving the normalization of the circadian sleep/wake system.…”
Section: Remediating Stress-related Endophenotypes Of Suicide: a Pote...mentioning
confidence: 99%
“…Reduced SI by reducing insomnia, sleep restlessness, early morning waking, and nocturnal wakefulness ( Rodrigues et al, 2021 ; Vande Voort et al, 2016 )…”
Section: Introductionmentioning
confidence: 99%
“…10 Furthermore, persistent insomnia was reported to be a predictor of depression relapse and may contribute to refractory depression. 11 A meta-analysis review revealed that poor sleep quality, defined as an individual having shorter or longer sleeping times than normal, may increase the risk of morbidity related to depression. 12 These findings indicate that sleep disturbance can be considered a potential therapeutic target for improving the symptoms and progression of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…12 Researchers have found that the antidepressant effects of ketamine were associated with decreased wakefulness, increased slow-wave activity, total sleep, and rapid eye movement sleep in MDD patients. 13 Ketamine infusions induced better therapeutic effects in sleep responders than in sleep nonresponders and patients without sleep disturbances. 14 Scholars found that improvement of sleep quality may be related to rapid improvement in depressive symptoms.…”
mentioning
confidence: 99%